Carbon Plate Shoes Improve Metabolic Power and Performance in Recreational Runners - Nielsen, Anders; Franch, Jesper; Heyde, Christian; de Zee, Mark; Kersting, Uwe; Larsen, Ryan Godsk (International Journal of Sports Medicine, 2022)
This study compared metabolic power (MP) and time trial (TT) running performance between Adidas Adizero Adios (AAA) and Nike VaporFly 4% (NVP). Thirty-seven runners completed three laboratory sessions and two field sessions (n=30). After familiarization (visit 1), participants completed eight 6-min treadmill running bouts (four with each shoe, counterbalanced) at their preferred pace, and MP was assessed using indirect calorimetry (visits 2 and 3). During visits 4 and 5, participants completed two outdoor TTs (~3.5 km) in NVP and AAA (counterbalanced). Compared with AAA, NVP exhibited superior MP (NVP: median=13.88 (Q1–Q3=12.90–15.08 W/kg; AAA: median=14.08 (Q1–Q3=13.12–15.44 W/kg; z=−4.81, p<.001, effect size=.56) and TT (NVP=793±98 s; AAA=802±100 s, p=.001; effect size=.09). However, there was no relationship between changes in MP and changes in TT between shoes (r=.151 p=.425, 95% confidence interval=[−.22; .48]). Our results demonstrate that NVP, compared with AAA, improves MP and TT in recreational runners. The lack of correlation between changes in MP and TT indicates that factors other than improved MP contribute to faster short-distance TT with NVP.
Keywords: running shoes; nike vaporfly; adidas adios; running economy; running performance